2015
DOI: 10.1002/2327-6924.12151
|View full text |Cite
|
Sign up to set email alerts
|

A Pap test does not screen for everything: Nurse practitioner knowledge of ovarian cancer

Abstract: Purpose Nurse practitioners (NPs) are in a prime position to educate women about initial signs and symptoms of ovarian cancer (OC) and perform appropriate screening tests. However, little is known about NPs knowledge regarding OC. This article's purpose is to present the outcomes of a focused OC awareness program for NP students. Data sources NP students (N = 104) participated in this longitudinal one group pre–post study. Knowledge was calculated based on the number of correct answers for a total knowledge sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Loerzel et al demonstrated knowledge deficits in NP students and identified a paucity of literature for NPs on early detection strategies. 28 In their study, as in ours, the majority of respondents (68%) believed that a Pap test screened for ovarian cancer. Loerzel et al identified knowledge deficits among NP students who had not completed training.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Loerzel et al demonstrated knowledge deficits in NP students and identified a paucity of literature for NPs on early detection strategies. 28 In their study, as in ours, the majority of respondents (68%) believed that a Pap test screened for ovarian cancer. Loerzel et al identified knowledge deficits among NP students who had not completed training.…”
Section: Discussionmentioning
confidence: 52%
“…As primary care delivery continues to incorporate NPs and PAs as major partners of the care team, they will be tasked with preventive screening as well as early identification of disease. 15,28,30 In its landmark report, The Future of Nursing: Leading Change, Advancing Health, the Institute of Medicine (IOM) proposed that nurses be encouraged to practice to the full extent of their education and that they serve as full partners in the redesign and improvement efforts of the health care system. 31 When viewing ovarian cancer from an epidemiologic perspective, it is clear that NPs and PAs should be able to function in both primary and secondary spheres.…”
Section: Discussionmentioning
confidence: 99%